2006
DOI: 10.1111/j.1600-0447.2006.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression assessed over 1‐year survival in patients with myocardial infarction

Abstract: Ten per cent of MI-patients fulfilled diagnostic criteria for depression at discharge. There was a significant trend for increasing mortality with increasing severity of the depressive episode. All mortality among depressed patients was seen in patients with non-Q-wave infarction. These findings indicate future studies in selected subgroups of MI-patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
(52 reference statements)
0
7
0
1
Order By: Relevance
“…Only eight studies [26][33] provided adjusted estimates and they were too heterogeneous to pool into a common estimate. In these studies, the estimates were on average 21% lower after adjustment for cardiac disease severity and comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Only eight studies [26][33] provided adjusted estimates and they were too heterogeneous to pool into a common estimate. In these studies, the estimates were on average 21% lower after adjustment for cardiac disease severity and comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…61,62 Another 60 found that the association was signifi cant for older (older than 65 years) but marginal for younger patients. Studies of similar methodological quality published since the EPC report have shown relations between post-MI depression symptoms and hospital readmission 21,26,29 and nonfatal cardiac events or symptoms. 8,13 Two adequately powered studies 26,29 did not support the relation between depression and nonfatal events.…”
Section: Evidence Question 2: What Is the Prevalence Of Continued Depmentioning
confidence: 95%
“…Sorensen et al. (4), in this issue, assessed depression over the course of 1 year in patients with an episode of myocardial infarction (MI), including non‐Q‐wave (intramural) MI and Q‐wave (transmural) MI. Of a total of 763 patients who had been admitted to 17 Danish hospitals for MI, 73 (9.6%) fulfilled ICD‐10 criteria for depression at discharge from the index hospitalization, based on their responses to the major depression inventory, a self‐administered questionnaire for depression with proven reliability for detecting a diagnosis of depression.…”
Section: Introductionmentioning
confidence: 99%
“…The depression‐positive group was more likely to require re‐hospitalization during the 1‐year study period, although they were no more likely than their non‐depressed counterparts to have another acute coronary event. Severity of depression – mild, moderate, or severe – did not separate by sex, age, or cardiovascular risk profile but was associated with increased mortality (4). The relative risk (RR) was 3.2 for death during the 1‐year follow‐up compared with patients without depression at index discharge.…”
Section: Introductionmentioning
confidence: 99%